Огляд методів нормалізації зображення - Фролов, Д. Є. (ХНУРЕ, 2024)
Image processing using to improve the quality of images, edit colors and effects, and correct imperfections in photos. In image processing systems, image enhancement is performed using a variety of techniques. Image normalisation techniques are using to enhance images. The main methods are related to changes in contrast, lighting, and noise removal. Each of these methods can be applied separately or in combination with others. Convolutional Neural Networks and semantic segmentation are aimed at eliminating the disadvantages of using normalisation methods.
Keywords: нормалізація зображення